A Common First-Year Undergraduate Engineering Course in Manufacturing based on Industrial Robots and Flipped Classroom. (September 2022) - Funes-Lora, Miguel A.; Fu, Albert Q.; Webster, Noah; Burcon, Sarah; Shih, Albert J.
Abstract: The pedagogy of a first-year engineering course in manufacturing is presented. This course entitled Manufacturing and Society involves collaboration with social science, is based on industrial robots as the central theme to attract students' interests and utilizes the flipped classroom approach for delivery. We hypothesize that, in one semester, recent high school graduates will be able to gain knowledge in manufacturing by learning the computer-aided engineering (CAD) software, applying CAD to design a penholder, fabricating the penholder using additive manufacturing and computer-aided manufacturing (CAM) software, programming the robot to create a toolpath for the pen, drawing using the pen on the penholder guided by a robot, and elaborating on impacts of robotic painting on society from a social science perspective. This course is designed to give students, regardless of their intended major in engineering, broad knowledge in manufacturing via 10 engineering, 3 social science, and 10 technical communication lectures; 8 labs; and 4 projects. The social science lectures and discussions focus on how knowledge about society can be used to inform design and manufacturing decisions, social science research methods for understanding how engineers and technology can impact people's lives, and changing trends in work, the workplace, and the future workforce as it relates to manufacturing. This course aimed to give undergraduate first-year engineering students a positive view of advanced manufacturing and its impact on society. Student evaluations and comments were positive and affirmed the learning objective of teaching manufacturing to the first-year engineering students. The flipped classroom approach was demonstrated to be ideal during the COVID-19 pandemic with limited capacity for in-person lectures and labs. The use of flipped classrooms allowed students to learn at their own pace, review and reinforce knowledge, have a closer interaction with instructors, and reduce the number of technical errors using simulation tools. This course with the support of flipped classroom pedagogy can be successfully implemented in the post-pandemic era, devoting the time of the class to answer questions, expand upon the class content and have a closer in-person interaction with students.